Short Communication The Study of Electrolytes on the Dye Uptake of Bifunctional Reactive Red Dyes on a Cellulosic Substrate (Cotton K-68) (Biological Sciences - PJSIR, 2006)
For obtaining optimum conditions for dyeing a cellulosic substrate (cotton K-68) with bifunctional reactive dyes, it was investigated as to how the dyeing results depended upon the properties of the dyes and the substrate. A cellulosic substrate (cotton K-68) was dyed by varying the nature and quantity of electrolytes. Experimental findings indicated that sodium chloride and sodium sulphate produced good dye exhaustion. An increase in the concentration of electrolytes (sodium chloride, sodium sulphate and potassium chloride) also improved the fastness properties of the dyed substrate.